The girl who could silence the wind - Medina, Meg 1963- (Walker, 2012)
On the night Sonia Ocampo is born, the village folk of Tres Montes survive the most horrific storm they have ever seen. Immediately they believe Sonia must possess a special gift to heal and protect. But after a young boy dies despite her prayers, sixteen-year-old Sonia is filled with shame and a sense of utter powerlessness. The hundreds of tiny gold symbols pinned to her shawl now only seem like empty, superstitious charms. At once she longs to escape a life built on lies. With the help of her aunt, Sonia takes a train to the city to begin a post in the household of a wealthy woman. Perhaps all their fortunes will now improve? However, a short time later Sonia hears the devastating news that her brother has gone missing from the village. It is not the first time a young man has disappeared in the region, and everyone knows all too well what his fate may be. Sonia must now risk absolutely everything to find him, and find a way to bring him home. 12 yrs+
Keywords: Families / Mexico / Fiction; Identity (Philosophical concept) / Fiction; Mexiko